Strategi Pemasaran Apel Malang - Relawati, Rahayu; Masyhuri, Masyhuri; R. Waluyati, Lestari (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2019)
This study aims to formulate the marketing strategy of Malang apple. The research subjects are traders and farmers of Malang apple in Malang Raya. Meanwhile the primary data was analyzed by the SWOT analysis. The result shows that the strengths of the Malang apple compared to the imported one are fresher, healthier and relatively cheaper, but the weaknesses are the less interesting of the apple?s appearance and purchasing place, and also the less promotion. Meanwhile, the opportunities are the better consumer?s purchasing power and their health motivation, and the increasing of Malang apple demand. However, the threats from the imported apple are the more interesting, the consumers? prestige motivation, and the increasing number. The marketing strategy of Strength-Opportunity is recommended. The recommendation includes: 1)the implementation of Good Agricultural Practices to increase the total production, higher grade and organic apple; 2)the marketing of organic apple with premium price; 3)keeping the freshness and appearance of Malang apple along the marketing channel; 4)the better display and on-line delivery order of Malang apple to increase its prestige and market segment of young generation; 5)the promotion through internet about the health benefit of Malang apples; 6)a limitation of imported apple number with a quality selection.